Utilization of Biochar and Mycorrhiza to Increase the Absorption of Elemental Nutrients of Cayenne Chili Plant (Capsicum fruntescnes L.) - Giono, Bibiana Rini Widiati; Solle, Muchtar Salam; Idrus, Muhammad Izzdin; Sofyan, Sofyan (UNIVERSITY OF LAMPUNG, 2021)
This study aimed to obtain the composition of biochar as a soil enhancer and mycorrhizal dose, which affected the nutrient uptake of cayenne plants. This experimental research was based on a separate plot design (RPT) with a basic randomized block design (RCBD). The main plot experiment was vesicular-arbuscular mycorrhiza or VAM (m) with three levels: mycorrhiza 10 g/plant (m1), mycorrhiza 15 g/plant (m2), and mycorrhiza 20 g/plant (m3). The subplot is biochar composition as soil enhancer (b) with three types: biochar husk 50%+25% soil+25% sand (b1), 50% sand+25% soil+25% biochar wood (b2), and wood charcoal biochar 50%+soil 25%+biochar charcoal husk 25% (b3). Each level of the VAM doses factor is combined with biochar. These nine treatment combinations and the levels were repeated thrice, accounting for 27 experimental units. The results showed that the parameters of phosphorus uptake, potassium uptake, and fresh root weight had a positive and significant relationship to the percentage of mycorrhizal infections. The combination treatment of mycorrhiza 20 g/plant and the composition of 50% husk biochar+25% soil+25% sand, 15 g mycorrhizal dose treatment with 50% wood biochar+25% soil+25% biochar rice husk and 20 g/plant are the best treatment as a planting medium.